2009
DOI: 10.1021/jf900836b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Kinetics of Anthocyanins from Blood Orange, Blackberry, and Roselle Using the Arrhenius, Eyring, and Ball Models

Abstract: Anthocyanin stability was assessed over temperatures ranging from 30 to 90 degrees C for seven products: blood orange juice [Citrus sinensis (L.) Osbeck]; two tropical highland blackberry juices (Rubus adenotrichus Schlech.), one with high content and the other with low content of suspended insoluble solids (SIS); and four roselle extracts (Hibiscus sabdariffa L.). The blackberry juice showed the highest content of anthocyanins with 1.2 g/L (two times less in the roselle extracts and 12 times less in the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
113
5
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 40 publications
15
113
5
15
Order By: Relevance
“…Therefore, parameters (especially temperature and time) should be optimized during thermal processes, such as drying (Sabarez and Henry, 2014). Some studies have indicated a considerable reduction in the anthocyanin content of some fruits occurs during different heating processes (Cisse et al, 2009;Bener et al, 2013;Ozturk et al, 2014).…”
Section: Thermal Degradation Kinetics Of Grapes Anthocyaninmentioning
confidence: 99%
“…Therefore, parameters (especially temperature and time) should be optimized during thermal processes, such as drying (Sabarez and Henry, 2014). Some studies have indicated a considerable reduction in the anthocyanin content of some fruits occurs during different heating processes (Cisse et al, 2009;Bener et al, 2013;Ozturk et al, 2014).…”
Section: Thermal Degradation Kinetics Of Grapes Anthocyaninmentioning
confidence: 99%
“…It has been found that increasing the temperature for extraction, up to 80 °C, increases the yields of total phenols in soy extracts using soy powder with an average particle size of 0.459 mm (Jokić et al, 2010). However, the use of temperatures higher than 70 °C for prolonged periods may cause significant degradation of anthocyanins (Cissé, Vaillant, Acosta, Dhuique-Mayer, & Dornier, 2009;Gartaula & Karki, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cisse et al (2009) explained that anthocyanins of Rubus adenotrichus are less sensitive to heat when compared to anthocyanins from other fruits and other varieties of blackberry. Hager et al (2008) reported a decrease in the scavenging activity against peroxyl radicals and superoxide radicals (ORAC and PCL) after thermally processed blackberry products, but not after storage time.…”
Section: Introductionmentioning
confidence: 99%